Influence of Macrocyclic Ring Size on the Corrosion Inhibition Efficiency of Dibenzo Crown Ether: A Density Functional Study - Saprizal Hadisaputra; Saprini Hamdiani; Muhammad Arsyik Kurniawan; Nuryono Nuryono (Universitas Gadjah Mada, 2017)
The effect of macrocycle ring size on the corrosion inhibition efficiency of dibenzo-12-crown-4 (DB12C4), dibenzo-15-crown-5 (DB15C5), dibenzo-18-crown-6 (DB18C6), dibenzo-21-crown-7 (DB21C7) and dibenzo-24-crown-8 (DB24C8) have been elucidated by mean of density functional calculation at B3LYP/6-31G(d) level of theory in the gas and aqueous environment. The quantum chemical parameters including the frontier orbital energies (EHOMO, ELUMO), ionization potential (I), electron affinity (A), the absolute electronegativity (χ), hardness (η), softness (σ), and the fraction of electron transferred (ΔN) are positively correlated to the corrosion inhibition efficiency (IE%) of the studied crown ethers. The calculation results indicate that DB24C8 exhibits the highest corrosion inhibition efficiency, whereas DB12C4 exhibits the lowest corrosion inhibition efficiency. The results of this study will contribute to design crown ethers potential as corrosion inhibitors.